Contemporary trends in mortality related to high-risk pulmonary embolism in US from 1999 to 2019 - Zuin, Marco; Bikdeli, Behnood; Davies, Julia; Krishnathasan, Darsiya; Rigatelli, Gianluca; Roncon, Loris; Bilato, Claudio; Piazza, Gregory (Thrombosis research, 2023)
Population-based data on high-risk pulmonary embolism (PE) mortality trends in the United States (US) are scant. To assess current trends in US mortality related to high-risk PE over the past 21 years and determine differences by sex, race, ethnicity, age and census region. Data were extracted from the Centers for Disease Control and Prevention (CDC) Wide-ranging ONline Data for Epidemiologic Research (WONDER) to determine trends in age-adjusted mortality rates (AAMR) per 100,000 people, due to high-risk PE. To calculate nationwide annual trends, we assessed the average (AAPC) and annual percent change (APC) with relative 95 % confidence intervals (CIs) using Joinpoint regression. Between 1999 and 2019, high-risk PE was listed as the underlying cause of death in 209,642 patients, corresponding to an AAMR of 3.01 per 100,000 people (95 % CI: 2.99 to 3.02). AAMR from high-risk PE remained stable from 1999 to 2007 [APC: −0.2 %, (95 % CI: −2.0 to 0.5, p = 0.22)] and then significantly increased [APC: 3.1 % (95 % CI: 2.6 to 3.6), p < 0.0001], especially in males [AAPC: 1.9 % (95 % CI: 1.4 to 2.4), p < 0.001 vs AAPC: 1.5 % (95 % CI: 1.1 to 2.2), p < 0.001]. AAMR increase was more pronounced in those <65 years, Black Americans, and residents of rural areas. In an US population analysis, high-risk PE mortality rate increased, with racial, sex-based, and regional variations. Further studies are needed to understand root causes for these trends and to implement appropriate corrective strategies. [Display omitted] •High-risk pulmonary embolism (PE) mortality rate increased in US between 1999 and 2019.•The high-risk PE mortality trend showed racial, sex-based, and regional variations.•Differences across demographic groups and rural versus urban populations persist.